Cancelar ou não cancelar, eis a questão: uma análise das características da cultura do cancelamento através do julgamento de celebridades no Twitter - Mancoso, Kaique de Souza (2023)
This study aimed to unravel the primary characteristics of cancel culture. Given the contemporaneity of the subject and the limited literary resources, this research reveals the configurations and implications of this phenomenon, thereby contributing to an enhanced understanding of conversational dynamics on social networks. To achieve this, five cases of cancellations of Brazilian public figures in 2022 were analyzed: Monark, Deolane Bezerra, Gkay, Jade Picon, and Luísa Sonza. The selection of these celebrities originated from the analysis of digital articles regarding "celebrities canceled in 2022", with online documentary research procedures being one of the fundamental techniques for this stage. The methodology primarily combined content analysis and social network analysis techniques to investigate the conversations of each case on Twitter. Given the peculiarities of each event, posts mentioning the relevant public figure were identified and extracted, specifically during the weeks of these events. The data revealed a substantial presence of hate speech through posts containing attacks and insults directed at the celebrities, originating from a significant majority of canceling users. Furthermore, the investigation indicates that the supposed relationship between the phenomenon of cancel culture and the scheduling of identity and moral agendas did not always prove significant, suggesting the absence of substantial debate and a tendency to divert from topics during interactions. In reality, the users' efforts were concentrated on demanding penalties and consequences for the canceled individuals. Nonetheless, there are indications that the consequences of cancellations are more ephemeral than enduring, highlighting the volatile nature of cancellation episodes with limited transformative impact on society. The results also underscore that the multidimensionality of the subject enhances the complexity of its comprehensive understanding. This investigative journey contributes to future reflections on digital ethics, online responsibility, and behavior on social media.